A concept of fusion medicine-where Ayurveda meets Allopathy - Bibek Raj Parajuli; Sanjib Koirala (Journal of Karnali Academy of Health Sciences, 2021)
There is a constant debate on the efficacy of medical treatments using ayurveda versus allopathy. Staunch supporters of one method of treatment are quick to dismiss the other.  Ayurvedic medicines  are cheaper and have natural ingredients. Allopathic medicines are easily available in city areas. There are interactions  between ayurvedic and allopathic drugs if  taken together. Ingredients in herbs and dietary supplements may modify the intestinal pH or motility, inhibit or induce gut transporters or metabolizing enzymes and glucuronidation pathways. The fusion of ayurvedic and allopathic medicines has both advantages and disadvantages. There must be strict regulatory agencies to monitor the quality, purity, efficacy and potency of both ayurvedic and allopathic medicines.